Innovation in the air cargo sector: case studies of Estonia and Poland - Niine, Tarvo; Kolbre, Ene; Miina, Aleksandr; Dziugiel, Malwina (Transport, 2015)
Air cargo sector is a developing and dynamic field, where innovation can take place in a number of forms – in the sense of technology as well as processes and business model alterations. The forefront of innovation in the sector lies ‘at the top’, i.e. around international airfreight hubs. In contrast, this study is aimed at mapping out the situation on the example of two regional airport hinterlands in Eastern Europe: Tallinn (Estonia) and Katowice (Poland), to identify the level and types of innovation present in air cargo service providing companies in these regions. The hypothesis of this study is that the level of innovation in the air cargo sector in the regions in question is both benefiting the existing cargo customers and sufficiently supporting the entrepreneurship development by attracting new customers to locate in the area and utilise air transport for their export despite the regions not being airfreight hubs in international sense. A survey was designed and conducted involving altogether 32 companies in the air cargo sector in Estonia and Poland and was carried out in the beginning of 2013. Additional information was obtained by expert interviews with selected participants in the framework of Baltic Air Cargo Network (BACN). The perceived level of innovation in both regions is relatively high in most types of innovation. Various improvements are mostly resulting in increased service quality and differentiation by quality rather than service price. Selected statistically, significant differences in data of two countries allow to understand two similar environments better. The outlooks of the sector in the regions are cautiously optimistic and the developments affect the existing exporters as well as create a suitable environment to attract new exporters and enable entrepreneurship growth in the future. It is interesting and valuable to air cargo stakeholders and authorities that air cargo service industry can be innovative and has growth potential even in regions with the modest number of direct flight destinations. Innovation comes to life via flexibility in transport services, such as the growth and systematic development of Road-Feeder Services (RFS), which allows remote regions to be better connected in the international networks.